Collaborative multi-stakeholder spaces to learn about socio-technical bundling - Puskur, Ranjitha; Nchanji, Eileen; Cosmas, Lutomia; Ketema, Dessalegn; Muteti, Thomas; Gartaula, Hom; Mukhopadhyay, Prama; Mapedza, Everisto D.; Chadha, Deepali (CGIAR System Organization, 2024)
Learning labs to promote spaces for learning and reflection among stakeholders including development agencies, farmers and researchers on the gender-responsive socio-technical innovation bundling approach to enhance resilience of women farmers, empowerment and food security.